Transformation from a Western to an African style of leadership in Eskom - South Africa - Tobias, Lloyd Lester (My University, 2011)
Following the political transformation of the 1994's first democratic election, South Africa is making determined strides to establish a culture of democracy in conjunction with the economic trasformation of the country. The transformation to democracy has presented South African organisations with a myriad new opportunities and threats. Consequently, leaders of these organisations have been forced to learn rapidly to handle situations differently while simultaneously leadng people, driving transformation and effectively managing performance of their organisations...
MBA - WBS
Keywords: Leadership styles